PRIMER REGISTRO DE LIGIA BAUDINIANA (CRUSTACEA: ISOPODA: ONISCIDEA) PARA EL CARIBE COLOMBIANO (Boletín de Investigaciones Marinas y Costeras, 2016)
The isopod Ligia baudiniana is reported for the first time from the Caribbean coast of Colombia. Specimens of this species were collected on a rocky, intertidal substrate on the beaches of Marbella, Cartagena de Indias. A diagnosis is included along with illustrations of main taxonomic characters.